(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Electronic devices like, smart mobiles, smart boards, and laptops contributed to making English language learning easier, and they facilitated continuous individual training and skills development. So students can get the benefits of these technologies by knowing the appropriate ways to use these electronic devices. For that, the companies that manufacture these electronic devices provide more and more wonderful applications for learning the English language through these applications, students can learn the English language easily in a short time by themselves without a teacher.